Conversion of Tanah Bengkok Land into a Market in Kalikarung Village, Wonosobo Regency: Pengalihan Fungsi Lahan Tanah Bengkok Menjadi Pasar Di Desa Kalikarung Kabupaten Wonosobo - Amrullah, Heru Pratama Adnan; Irawaty, Irawaty (Annual Review of Legal Studies, 2024)
The conversion of bengkok land into a market is an action taken by village officials using village land in the form of bengkok land to build public facilities, namely traditional markets. This study uses a qualitative approach method with empirical legal research. Data was obtained through the Kalikarung Village Apparatus and local residents through interview techniques and literature sources. The purpose of this study is to find out and analyze the conversion of the function of agricultural land in the village of bengkok in Kalikarung based on its function which was originally agricultural land used or aimed at increasing the income of village officials, namely the results of managing the agricultural land are converted into a traditional market aimed at the prosperity of village residents and to find out and analyze the impact of the conversion of the function of the bengkok land. The bengkok land managed by the village apparatus is a source of additional income for the village apparatus itself, but in Kalikarung Village, Kalibawang District, Wonosobo Regency, in managing the bengkok land there is a policy that does not provide certainty regarding the results of managing the bengkok land into a traditional market to the village apparatus and also the community who participate in managing the traditional market. The process of land conversion in Kalikarung village has been carried out and a traditional market has been built on the village's bengkok land, but in its implementation there are problems regarding the distribution of profits from the traditional market, namely the absence of provisions regarding levies for building tenants in the market and their distribution to those who are entitled to receive it.